Alteration of the liver blood flow and phagocytic activity of the reticuloendothelial system in monkeys infected with Plasmodium knowlesi - S. Areekul (2018)
131 I labelled aggregated human albumin ( 131 I AA) was used to measure the liver blood flow and the phagocytic activity of the RES in rhesus monkeys infected with P. knowlesi in comparison with normal monkeys. The results showed that 131 I AA was phagocytized by the RES according to an exponential function of the blood concentration in relation to time. The liver blood flow was found to be slightly but not significantly diminished in the infected monkeys in relation to the normal group. There was a significant difference in the mean value of the phagocytic index (K) in the infected group (0.124 min - ) compared to the normal group (0.056 min - ). The increased values of the phagocytic index were found to be normal in monkeys after treatment with anti malarial drugs. These findings indicated that there was a slightly diminished liver blood flow and an increased phagocytic activity of the RES in monkeys infected with P. knowlesi and this activity returned to normal values after recovery from malaria.